2009
DOI: 10.1111/j.1365-2095.2008.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

No significant effect of additive ratios of docosahexaenoic acid to eicosapentaenoic acid on the survival and growth of cobia (Rachycentron canadum) juvenile

Abstract: An experiment was conducted in the laboratory to investigate the effects of additive ratios of docosahexaenoic acid (DHA) to eicosapentaenoic acid (EPA) on the growth and survival of cobia (Rachycentron canadum) juveniles from August to October 2005. Three hundred and eighty cobia juveniles (56 days of age, body weight 6.9 ± 0.1 g, body length 9.2 ± 0.1 cm) were selected and 20 of them were freely taken for initial sample analysis in the week 0. Additional 360 juveniles were randomly assigned into eight groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(97 reference statements)
2
10
0
Order By: Relevance
“…A similar finding was reported for Dicentrarchus labrax, in an experiment by which fish received the same amount of fishmeal, and fish oil source was replaced by soybean oil (Hunt & Tekelioglu, 2008). Similar results were also shown for Rachycentron canadum, for which the higher amounts of diet-supplementation with EPA and DHA than those already present in fishmeal did not improve fish performance (Ding et al, 2009).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…A similar finding was reported for Dicentrarchus labrax, in an experiment by which fish received the same amount of fishmeal, and fish oil source was replaced by soybean oil (Hunt & Tekelioglu, 2008). Similar results were also shown for Rachycentron canadum, for which the higher amounts of diet-supplementation with EPA and DHA than those already present in fishmeal did not improve fish performance (Ding et al, 2009).…”
Section: Resultssupporting
confidence: 73%
“…The lack of long-chain fatty acids in vegetal oils might have been overcome by the diet formulated with 52% marine fishmeal, which provided about 2.5‰ EPA and 5.4‰ DHA to the diet. These values are close to the ones used in feed formulas distributed to other marine species (Peng et al, 2008;Ding et al, 2009), suggesting that, depending on the diet composition, supplementation with EPA and DHA might be unnecessary to feed juveniles of fat snook. Similar results have also been reported for Solea senegalensis (Borges et al, 2014).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…A study on cobia (Ding et al . ) showed that the growth of juvenile cobia was not greatly influenced by ratios of DHA to EPA since a high content of dietary fishmeal (67%) used in the study probably have met the requirement of n‐3 LC‐PUFAs in cobia and masked the effects of the additive DHA and EPA.…”
Section: Discussionmentioning
confidence: 85%
“…This made the present study more worthwhile for the farmers since the difference between DHA and EPA in their effects on fish was always species‐specific and easily influenced by rearing conditions (Koven, Tandler, Sklan & Kissil ; Tago et al . ; Villalta & Estévez ; Ding, Xu, Zhang, Wang, Chen & Sun ; Dantagnan et al . ; Trushenski et al .…”
Section: Introductionmentioning
confidence: 99%